KONSEP ILMU DALAM ISLAM: TINJAUAN TERHADAP MAKNA, HAKIKAT, DAN SUMBER-SUMBER ILMU DALAM ISLAM - Muhammad Zainal Abidin (Jurnal Ilmiah Ilmu Ushuluddin, 2011)
This paper tries to explore the concept of knowledge (ilm) in Islam. There are twoaspects that will be discussed here. Both are the view of meaning and the essence ofknowledge in Islam and the sources of knowledge in Islam. The first one speaks aboutthe ontological aspect and the second one discusses about epistemological aspect. This articleshows that the research that the concept of knowledge in Islam is similar with theconcept of science in western tradition, but with the wider scope. Seeing in knowledgesources, there are three aspects that can be explored, those are the signs of qauliyyah (thewords of God), the signs of kauniyyah (the world of God), and the signs of insniyyah.